THE ANALYSIS OF PT INDOFOOD'S INDOMIE PRODUCT MARKETING STRATEGY IN INCREASING PROFITABILITY - Muhammad Sukron; Intan Vianidya; Zahvie Nur Septiyani; Putri Jasmine Rofik; Vera Sylvia Saragi Sitio (Desanta Publisher, 2025)
This study aims to analyze the effect of marketing strategies implemented by PT Indofood on the profitability of Indomie products, This study uses a quantitative approach, using a combination of descriptive analysis to introduce basic data and inferential analysis to find relationships between variables, as well as distributing questionnaires distributed to respondents. Respondents in this study were consumers of indomie products with a sample size of 50 respondents. Data analysis using multiple linear regression techniques assisted by the SPSS version 25 program. The results of the study through the F test, the Fcount value was obtained (9.843) and Ftable (2.58), it is known that the significance in the F test is 0.000 which is the significance limit of 0.05. So the conclusion is that the hypothesis results are accepted or in other words the independent variables (Free), namely Product (X1), Price (X2), Place (X3), and Promotion (X4) simultaneously affect the dependent variable (bound), namely Profitability (Y).